Mutual Dependence between Sustainable Energy- and Sustainable Agriculture Policies-from the Global and European Perspective - Wysokińska, Zofia (Comparative Economic Research. Central and Eastern Europe, 2012)
The aim of the paper is to present the interrelationship between the sustainable energy, especially renewable energy sector and sustainable agriculture policy from both: the European and the global perspectives. In the world and European economy the role of Renewable Energy Technologies is still increasing. Energy efficiency; sustainable agriculture; renewable energies for rural development belong to main poles of sustainable development in the world economy and its regions. Agriculture is one of the economic sectors to which the EU commitment to reduce emissions of greenhouse gases applies. Like any other economic sector, agriculture produces greenhouse gases and is a major source of the non- CO2 greenhouse gases methane and nitrous oxide. It is also the strong relationship between the sustainable agriculture sector and the renewable energy development possibilities. The sustainable agriculture can be seen as a source of renewable energy.